2011
DOI: 10.1111/j.1365-2710.2011.01258.x
|View full text |Cite
|
Sign up to set email alerts
|

A patient’s perspective: the impact of adverse drug reactions on patients and their views on reporting

Abstract: Patients having a severe adverse drug reaction following an acute illness felt negative emotions towards their health care provider. Those with a chronic condition rationalized the event and coped better with its impact. Neither group felt that reporting the adverse reaction was their responsibility. Encouraging patients to report remains important but expecting patients to report solely for altruistic purposes may be unrealistic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 8 publications
2
51
0
2
Order By: Relevance
“…However a minority felt that in order to confirm causality assessment of their ADRs, patients should report ADR to healthcare professionals first. A similar view was expressed by some patients in a qualitative UK study [20] who considered that ADR reporting was a task for health professionals and not their responsibility, whereas the prevailing concern in our study was the quality of reports and certainty of the association. Altruistic reasons were mentioned by most interviewees, with only a minority expressing the view that it was an opportunity for personal gain, which is in line with other studies in UK and the Netherlands [13,[21][22][23].…”
Section: Main Findingssupporting
confidence: 76%
“…However a minority felt that in order to confirm causality assessment of their ADRs, patients should report ADR to healthcare professionals first. A similar view was expressed by some patients in a qualitative UK study [20] who considered that ADR reporting was a task for health professionals and not their responsibility, whereas the prevailing concern in our study was the quality of reports and certainty of the association. Altruistic reasons were mentioned by most interviewees, with only a minority expressing the view that it was an opportunity for personal gain, which is in line with other studies in UK and the Netherlands [13,[21][22][23].…”
Section: Main Findingssupporting
confidence: 76%
“…A survey of 661 outpatients in Boston identified that 37% of ameliorable ADRs were related to failure of service users to inform physicians (19/51) [30]. Public awareness of ADR reporting remains low [31], [32]: a survey of 2028 UK adults indicated that while 477 (24%) had experienced an ADR, only 172/2028 (9%) were aware of reporting mechanisms [33], [34]. ADR reporting by physicians may retain an element of subjectivity [35], [36], and the long-term effects of educational interventions to increase ADR reporting are unclear [37].…”
Section: Introductionmentioning
confidence: 99%
“…Some pilot qualitative work carried out in patients admitted to hospital with serious ADRs has found reporting the suspected ADR was not viewed as a priority by patients, and was described as the doctor's job. 5 Reports from patients are therefore complimentary to, not a replacement for, reports from healthcare professionals.…”
Section: Evidence Supporting Patient Reportingmentioning
confidence: 99%